(untitled) (Jurnal Pendidikan Fisika, 2026)
Critical thinking is one of the essential competencies in physics education because it enables students to analyze phenomena, evaluate evidence, and draw logical conclusions in scientific learning. However, students’ critical thinking skills in physics remain relatively low, partly because instructional practices are still often dominated by single-method and teacher-centered approaches. This study aimed to develop and evaluate a multi-methods discovery-learning strategy to enhance senior high school students’ critical thinking skills in physics. The study employed a research and development approach using the ASSURE instructional design model, followed by a quasi-experimental posttest-only control group design. The participants were 64 eleventh-grade students in the physics specialization program at a public senior high school in Majene, Indonesia, divided into an experimental group and a control group, with 32 students in each class. The instruments included expert validation sheets, a learning implementation observation sheet, teacher and student response questionnaires, and a critical thinking skills test. Data were analyzed using descriptive analysis, Aiken’s V, and an independent samples t-test with the assistance of SPSS version 26. The results showed that the developed strategy met the criteria of validity, practicality, and effectiveness. Expert judgment indicated that the learning materials and instruments were valid, while teacher and student responses confirmed the strategy’s practicality. Furthermore, the t-test results revealed a statistically significant difference in critical thinking scores between the experimental and control groups. The novelty of this study lies in the systematic integration of expository, practicum, trial, and simple research methods within a structured discovery learning framework. In conclusion, the multi-methods discovery learning strategy is effective in improving students’ critical thinking skills. It makes a meaningful contribution to physics education by providing an integrative, student-centered instructional approach.